2022
DOI: 10.1111/petr.14296
|View full text |Cite
|
Sign up to set email alerts
|

Quadratus lumborum blocks for abdominal transplant surgeries at UPMC Children's Hospital of Pittsburgh—A five year experience

Abstract: Background: Adequate perioperative analgesia for pediatric abdominal transplant surgery is essential for patient recovery. However, the risks of commonly used medications such as hepatotoxicity, nephrotoxicity, bleeding concerns, and poor graft results with opioids limit pain management in this population. Thoracic epidural, continuous erector spinae plane, and type-1 quadratus lumborum blocks (QLBs) have been described and utilized in the adult population in this setting. The safety and benefits of regional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…These benefits appear to apply to both laparoscopic approaches as well as open approaches 50 . The use of QL blocks has also been demonstrated in pediatric patients undergoing renal transplantation, although this study of 32 patients did not include a control group for comparison 26 …”
Section: Discussion: Summary Of Regional Anesthesia For Transplantati...mentioning
confidence: 99%
See 2 more Smart Citations
“…These benefits appear to apply to both laparoscopic approaches as well as open approaches 50 . The use of QL blocks has also been demonstrated in pediatric patients undergoing renal transplantation, although this study of 32 patients did not include a control group for comparison 26 …”
Section: Discussion: Summary Of Regional Anesthesia For Transplantati...mentioning
confidence: 99%
“…These authors concluded that QL blocks are feasible in this patient population and can be used as an effective part of a postoperative pain regime. Further, these patients had a low complication rate, with the only noted complication of one hematoma in a kidney transplant recipient 26 . Further investigation into QL and RS blocks is required before this task force can recommend either in liver transplantation surgery, though the task force acknowledges both are likely safe and effective in treating postoperative liver transplantation pain.…”
Section: Discussion: Summary Of Regional Anesthesia For Transplantati...mentioning
confidence: 99%
See 1 more Smart Citation